Roof of Galeri Muzium Bukit Kepong, Muar / Salasiah Mohamad - Mohamad, Salasiah (2015)
The purposed of writing this report is to explain about roof which is roof has known as building envelope, both on the uppermost part of the building or shelter which provides protection from animals and weather, notably rain, but also heat, wind and sunlight and the framing or structure which supports the covering. The report also containing the introduction of industrial training which is included the objectives and benefits of industrial training to students. One of the benefits is gain work experience and transferable skills. In chapter 2, the report is about company background which is about JKR Muar. JKR Muar was located at Jalan Othman, Muar City. Chapter 2 also included the organizations charts, vision, mission and objectives. Meanwhile, in chapter 3, it is about literature review of roof. Which is including definition of roof, function of roof, basic types of roof, roof system, basic roof structure and basic type of roof trusses. Lastly in chapter 4, my case study is at Bukit Kepong which is project of Galeri Darurat 3 Tingkat. In this chapter, I will explain more about the roof structure that has been used to complete the gallery’s building.